Synthesis of libraries and multi-site mutagenesis using a PCR-derived, dU-containing template. Issue 1 (5th January 2021) - Meinke, Gretchen; Dalda, Nahide; Brigham, Benjamin S; Bohm, Andrew
Abstract: Directed DNA libraries are useful because they focus genetic diversity in the most important regions within a sequence. Ideally, all sequences in such libraries should appear with the same frequency and there should be no significant background from the starting sequence. These properties maximize the number of different sequences that can be screened. Described herein is a method termed SLUPT (Synthesis of Libraries via a dU-containing PCR-derived Template) for generating highly targeted DNA libraries and/or multi-site mutations wherein the altered bases may be widely distributed within a target sequence. This method is highly efficient and modular. Moreover, multiple distinct sites, each with one or more base changes, can be altered in a single reaction. There is very low background from the starting sequence, and SLUPT libraries have similar representation of each base at the positions selected for variation. The SLUPT method utilizes a single-stranded dU-containing DNA template that is made by polymerase chain reaction (PCR). Synthesis of the template in this way is significantly easier than has been described earlier. A series of oligonucleotide primers that are homologous to the template and encode the desired genetic diversity are extended and ligated in a single reaction to form the mutated product sequence or library. After selective inactivation of the template, only the product library is amplified. There are no restrictions on the spacing of the mutagenic primers except that they cannot overlap.